The Energy Challenge–Gone Today, Back Tomorrow: Maine’s Key Role - Hastings, William (Maine Policy Review, 2008)
World energy trends suggest that increased demand for fossil fuels is likely to continue, even as producers are not replacing what is being used. William Hastings argues that in spite of this, Maine is poised to potentially become an energy leader in the near future. He points out that a surprising number of new projects are increasing the diversity of the state’s energy supply.
Keywords: Maine; energy; pipelines